Antioxidant Activity of Flavonoids from Cassava Leaves (Manihot esculenta Crantz) - Enny Fachriyah; Ifan Bagus Haryanto; Dewi Kusrini; Purbowatiningrum Ria Sarjono; Ngadiwiyana Ngadiwiyana (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
The community uses cassava leaves for cooking because of their high protein content, β-carotene, Fe, Mg, Zn, S, Ca, Zn, Ni, and K. Cassava leaves contain various secondary metabolites, including flavonoids, saponins, tannins, phenolics, steroids, anthocyanins, and anthraquinones. The antioxidant activity of flavonoid compounds in cassava leaves (Manihot esculenta Crantz) has been successfully investigated. This study consisted of six stages: the preparation of ethanol extract of cassava leaves, phytochemical screening, determination of total flavonoid content in the extract, isolation of flavonoids, and purity testing of flavonoid isolates using the chromatographic method, identification of the structure of pure flavonoid isolates using a UV-Vis spectrophotometer with the addition of a shear reagent, FTIR, and LC-MS/MS. As well as test the antioxidant activity using the DPPH method. The yield of ethanol extract from cassava leaf in this study was 14.67%. The results of the phytochemical screening showed that the cassava leaves and the ethanol extract of cassava leaves contained alkaloids, flavonoids, saponins, tannins, quinones, steroids, phenolics, and triterpenoids. The total content of flavonoids in the ethanol extract was 35.71 mg EQ/g extract. UV-Vis, FTIR, and LC-MS/MS analysis revealed that the flavonoid isolate was quercetin. The results of the antioxidant activity of the ethanol extract and BC isolate showed IC50 of 81.76 ± 0.505 mg/L and 77.85 ± 4.708 mg/L.